Penerapan Sistem Kotak Saran Digital untuk Meningkatkan Partisipasi Warga dalam Evaluasi Pelayanan Publik (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out by lecturers of the College of Administrative Sciences (STIA) Satya Negara Palembang as part of fulfilling the obligations of the Tridarma of Higher Education, specifically in the aspect of community service. This program aims to increase citizen participation in public service evaluation by implementing a web-based digital suggestion box system at the Palembang City Tourism Office. This activity is motivated by the low effectiveness of conventional suggestion boxes, which are often less transparent, difficult to access, and slow to implement. Through a participatory approach and the use of digital technology, this system is designed to enable people to convey their aspirations, criticisms, and suggestions online with guaranteed identity confidentiality. The results of the implementation showed a significant increase in the number of suggestions, a reduction in response time from seven to two working days, and a community satisfaction rate of 92.74%. The implementation of this system also forms a more open and participatory pattern of public communication between the community and local governments. This activity has practical, academic, and policy implications as a model for implementing digital participatory governance that supports the principles of good governance and digital transformation of public services.